The Influence of Poverty, Dependency Ratio, and Gross Enrollment Rate on the Human Development Index in West Kalimantan - Dewi Laila Sari; Kukuh Arisetyawan (Jurnal Ilmu Ekonomi JIE, 2025)
This study aims to analyze the influence of poverty, dependency ratio, and gross enrolment ratio (GER) on the Human Development Index (HDI) in West Kalimantan from 2019 to 2023. Data from 12 districts and 2 cities between 2019 and 2023 were analyzed using a panel data regression with a random effects model (REM). The findings indicate that poverty and dependency ratios adversely and significantly affect HDI, whereas GER exerts a positive and substantial influence. All three variables exert a significant simultaneous influence on HDI. The practical application of this research lies in its ability to inform policy design for alleviating poverty, managing demographic structures, and improving educational accessibility, thereby accelerating human development in West Kalimantan.